2007
DOI: 10.1038/sj.onc.1210621
|View full text |Cite|
|
Sign up to set email alerts
|

Proliferation-associated Brn-3b transcription factor can activate cyclin D1 expression in neuroblastoma and breast cancer cells

Abstract: Brn-3b transcription factor enhances proliferation of neuroblastoma (NB) and breast cancer cell lines in vitro and increases the rate and size of in vivo tumour growth, whereas reducing Brn-3b slows growth, both in vitro and in vivo. Brn-3b is elevated in >65% of breast cancer biopsies, and here we demonstrate that Brn-3b is also elevated in NB tumours. We show a significant correlation between Brn-3b and cyclin D1 (CD1) in breast cancers and NB tumours and cell lines. Brn-3b directly transactivates the CD1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 38 publications
0
30
1
Order By: Relevance
“…It responds directly to mitogenic signals, and plays a critical role in cellcycle progression, especially during transition from G1 to the S phase [18]. Cyclin D1 has a rate-limiting role in G1-S phase transition, and plays a key role in malignant cell proliferation [45,46]. Our results indicated that c-myc and cyclin D1 were significantly downregulated by Wnt/β-catenin signaling when neuroblastoma cells proliferation was inhibited by WIF-1 restoration.…”
Section: Discussionmentioning
confidence: 68%
“…It responds directly to mitogenic signals, and plays a critical role in cellcycle progression, especially during transition from G1 to the S phase [18]. Cyclin D1 has a rate-limiting role in G1-S phase transition, and plays a key role in malignant cell proliferation [45,46]. Our results indicated that c-myc and cyclin D1 were significantly downregulated by Wnt/β-catenin signaling when neuroblastoma cells proliferation was inhibited by WIF-1 restoration.…”
Section: Discussionmentioning
confidence: 68%
“…For instance, Brn-3b may enhance proliferation by increasing transcription of cell cycle regulators, cyclinD1/ CDK4 (Budhram-Mahadeo et al 2008;Samady et al 2004) whilst inhibiting the tumour suppressor gene BRCA1 (Budhram-Mahadeo et al 1999), which induces cell cycle arrest in breast cancer cells. Brn-3b also regulates target genes that can alter cell motility and drug resistance, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As we did not investigate for the presence of p53 gene abnormalities, the mechanism that is responsible for the increase in the malignant potential of IDCs according to grades of lymph vessel tumor embolus from the standpoint of p53 gene abnormalities in lymph vessel tumor emboli, as well as in tumorstromal fibroblasts, or in stroma-invasive tumor cells should be investigated. In addition, as some studies have reported some identifying genes that closely regulate the cell cycle of tumors, [24][25][26] such genes should be investigated to determine whether they are candidates for p53 in regulating tumor cell cycle of lymph vessel tumor emboli.…”
Section: Discussionmentioning
confidence: 99%